An investigation of some variables problem solving skills of youth camps leaders - Coşkuner, Zeki (My University, 2013)
A problem is an obstacle, impediment, difficulty or challenge, or any situation that invites resolution; the resolution of which is recognized as a solution or contribution toward a known purpose or goal. Problem solving consists of using generic or specific methods, in an orderly manner, for finding solutions to problems. This research aims to examine if there is a significant difference between "the problem solving abilities" of some Youth Camps Leaders depending on variables such as age, gender, and experience. The sample of this investigation consists of 70 females and 114 males; 184 youth camps leaders who have attended the Ministry of Youth's sports camps. The statistics for Sahin and others were used to collect data and adapted for Turkish using the "Problem Solving Inventory". The data obtained was analyzed using the t-test and Anova tests and interpreted in the tables. According to the study of youth camp leaders, the results were impacted by several variables such as age, level of education, and gender differences.
Keywords: Problem; Problem Solving; Youth; Youth Camps